Colour-tunable quantum dots/poly(NIPAM-co-AAc) hybrid microgels based on electrostatic interactions. Issue 100 (14th October 2016) - Cai, Yuting; Du, Gaolai; Gao, Guorong; Chen, Jing; Fu, Jun
Abstract : Colour-tunable QD/poly(NIPAM- co -AAc) hybrid microgels have been synthesized by encapsulating and entrapping positively charged QDs with pH-responsive negatively charged microgels with tunable photoluminescent properties. Abstract : Monodisperse poly(NIPAM- co -AAc) microgels doped with either a monocolour photoluminescent quantum dot (QD) or multiple colour QDs have been fabricated by the charge-driven introduction of cysteamine-capped CdTe QDs and the collapse of the polymer network by adjusting the pH of the solution. The photoluminescence intensity and colour of the resulting microgels can be easily adjusted by changing the content of the CA–CdTe QDs in the hybrid microgels and using single or a mixture of different-sized QDs, respectively. In addition, the microgel-encapsulated QDs showed blue shifts, owing to surface coordination by the carboxylic acid. The combined effect of electrostatic interactions and surface chelating resulted in a reduction in microgel size. By tuning the ratio of QDs with different sizes, the photoluminescence of the hybrid hydrogels could be conveniently controlled. This work provides a facile and versatile method to fabricate colour-tunable or multifunctional hybrid hydrogels with broad potential applications.